The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3109/14992027.2015.1023903
|View full text |Cite
|
Sign up to set email alerts
|

Functional performance in older adults with hearing loss: Application of the International Classification of Functioning brief core set for hearing loss: A pilot study

Abstract: The ICF brief core set is a valuable tool for use in audiologic rehabilitation clinical practice and research design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
13
1
6
Order By: Relevance
“…To our best knowledge, two validation studies of ICF Core sets for HL have been identified. One of them, a pilot study by Alfakir, Holmes, and Noreen (2015) focussing on older adults (n ¼ 49) and based on data from audiological patient files and from two questionnaires, demonstrated good content and construct validity where 18 of the 27 ICF categories were represented (Alfakir, Holmes, and Noreen 2015). Furthermore, explorative factor analysis (EFA) using orthogonal rotation showed a four-factor solution explaining 59.8% of the variance.…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, two validation studies of ICF Core sets for HL have been identified. One of them, a pilot study by Alfakir, Holmes, and Noreen (2015) focussing on older adults (n ¼ 49) and based on data from audiological patient files and from two questionnaires, demonstrated good content and construct validity where 18 of the 27 ICF categories were represented (Alfakir, Holmes, and Noreen 2015). Furthermore, explorative factor analysis (EFA) using orthogonal rotation showed a four-factor solution explaining 59.8% of the variance.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the brief core set is more clinically friendly. 23 As highlighted in this case, the brief core set covers the commonly experienced functional and contextual factors relating to hearing loss. Nevertheless, the core sets are limited in that they do not currently consider or code the activity limitations and participation restrictions and contextual factors of significant others.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ICF offers broad structures and perspective on how audiological rehabilitation should be provided to older adults, 18 less has been published on the clinical use of the core sets for hearing loss. 23 The ICF contains over 4,000 codes for the description of the various aspects of body functions and structures, activities, participation and environmental factors, and the core sets include those codes most likely impacted by hearing loss. The comprehensive and brief core sets for hearing loss, as described in Meyer et al (this issue), offer a standard for hearing health professionals to document patients' functioning and a system for policy makers and researchers to quantify profiles of health conditions.…”
Section: Clinical Use Of the Icfmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is possible to infer how the ICF framework might apply to women with physical disabilities in and around the time of pregnancy, a search of the literature did not yield any articles describing how it would be applied with regard to pregnancy. 23-27 This gap in the literature suggests the need for a framework that applies a life span perspective in a manner that directly addresses the multiple determinants specific to women with physical disabilities around the time of pregnancy.…”
Section: Methodsmentioning
confidence: 99%